2018
DOI: 10.1111/jgh.13853
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol attenuates diet‐induced non‐alcoholic steatohepatitis by regulating macrophage polarization through activating peroxisome proliferator‐activated receptor γ

Abstract: Honokiol can attenuate CL diet-induced NASH and the mechanism in which possibly is polarizing macrophages to M2 phenotype via PPARγ activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…Recent studies have indicated that macrophages/Kupffer cells participate in lipid homeostasis in NAFLD. Animal studies have shown that M1 Kupffer cells increase hepatic lipid deposition, 39, 40 while M2 activation of Kupffer cells can ameliorate obesity‐induced insulin resistance and hepatic steatosis 41 . Furthermore, the promotion of hepatic M2 macrophage polarization was accompanied by attenuated hepatic lipid accumulation 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that macrophages/Kupffer cells participate in lipid homeostasis in NAFLD. Animal studies have shown that M1 Kupffer cells increase hepatic lipid deposition, 39, 40 while M2 activation of Kupffer cells can ameliorate obesity‐induced insulin resistance and hepatic steatosis 41 . Furthermore, the promotion of hepatic M2 macrophage polarization was accompanied by attenuated hepatic lipid accumulation 42 .…”
Section: Discussionmentioning
confidence: 99%
“…While most research suggests pro-inflammatory Mϕs dominate in NAFLD and drive disease pathogenesis, hepatic Mϕs may also have anti-inflammatory properties. Moreover, promoting such M2-like Mϕs has been reported to be beneficial for protecting against NAFLD [177] , [179] , [180] , [181] , [182] , [183] . Taken together, these results suggest that manipulation of the M1/M2 ratio in NAFLD may be an attractive therapeutic strategy [184] .…”
Section: Transcription Factors Modulating Lipid Metabolism Activity Imentioning
confidence: 99%
“…All three PPAR family members have been shown to play a role in mouse macrophage polarization. PPARα, β, or γ activation was demonstrated to potentiate the polarization of mouse macrophages towards the anti-inflammatory M2 phenotype, while M2-type responses are compromised in the absence of PPARγ or β expression (effect of PPARα absence has not been studied) [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. In human macrophages results are less clear-cut; while PPARγ activation has been shown to stimulate M2 polarization, PPARα or β activation did not seem to have any effect [ 67 , 68 , 69 , 70 , 71 ].…”
Section: Role Of Ppars In Immune Cell Functionmentioning
confidence: 99%